Cerebrovascular Events in Systemic Lupus Erythematosus: Results From an International Inception Cohort Study. Issue 10 (1st September 2018) - Hanly, John G.; Li, Qiuju; Su, Li; Urowitz, Murray B.; Gordon, Caroline; Bae, Sang‐Cheol; Romero‐Diaz, Juanita; Sanchez‐Guerrero, Jorge; Bernatsky, Sasha; Clarke, Ann E.; Wallace, Daniel J.; Isenberg, David A.; et al.
Abstract : Objective: To determine the frequency, characteristics, and outcomes of cerebrovascular events (CerVEs), as well as clinical and autoantibody associations in a multiethnic/racial inception cohort of patients with systemic lupus erythematosus (SLE). Methods: A total of 1, 826 patients were assessed annually for 19 neuropsychiatric (NP) events, including 5 types of CerVEs: 1) stroke, 2) transient ischemia, 3) chronic multifocal ischemia, 4) subarachnoid/intracranial hemorrhage, and 5) sinus thrombosis. Global disease activity (Systemic Lupus Erythematosus Disease [SLE] Activity Index 2000), damage scores (SLE International Collaborating Clinics/American College of Rheumatology Damage Index), and Short Form 36 (SF‐36) scores were collected. Time to event, linear and logistic regressions, and multistate models were used as appropriate. Results: CerVEs were the fourth most frequent NP event: 82 of 1, 826 patients had 109 events; of these events, 103 were attributed to SLE, and 44 were identified at the time of enrollment. The predominant events were stroke (60 of 109 patients) and transient ischemia (28 of 109 patients). CerVEs were associated with other NP events attributed to SLE, non–SLE‐attributed NP events, African ancestry (at US SLICC sites), and increased organ damage scores. Lupus anticoagulant increased the risk of first stroke and sinus thrombosis and transient ischemic attack. Physician assessment indicated resolution or improvement in the majority of patients, but patients reported sustained reduction in SF‐36 summary and subscale scores following a CerVE. Conclusion: CerVEs, the fourth most frequent NP event in SLE, are usually attributable to lupus. In contrast to good physician‐reported outcomes, patients reported a sustained reduction in health‐related quality of life following a CerVE.